Crocodile tears - Horowitz, Anthony, 1955- (Horowitz, Anthony, 1955- Alex Rider adventure., 2010)
"Targeted by a hitman and under threat of his past being exposed by the media, Alex reluctantly turns to MI6. But their help doesn't come cheap: they need Alex to spy on the activities at a GM crop plant. There he spots Desmond McCain, a high profile charity organiser, who realises that Alex is on to him and the real plans for the money he's raising. Kidnapped and whisked off to Africa, Alex learns the full horror of McCain's plot: to create an epic disaster that will kill millions. Forced to ask MI6 for protection, Alex finds himself being manipulated in a deadly game that could lead to the destruction of an entire East African country"--Amazon.com